Respons Jama’ah Terhadap Pengajian Kitab Tafsi - Ghozi Mubarok; Robi Sudrajat (Dirosat : Journal of Islamic Studies, 2019)
Recitation is a place to gain Islamic knowledge. In general, recitation is filled with reading the Koran, religious lectures, dhikr, learning the interpretation of the Koran, and so on. Recitations are usually held in mosques, but there are also those who hold recitations in langgars, mushallas or other places. During the course of the commentary study at the Mustaqbil Mosque, many processes were passed and elicited various responses from the congregation regarding the implementation of the recitation. Therefore, this study emphasizes the congregation's response to the implementation of the interpretation recitation and the congregation's motivation to take part in the Al-Sa'di interpretation recitation at the Mustaqbil Mosque. In this study, the type of research used by researchers is qualitative research to examine the phenomenon of the Living Qur'an. The data collection was obtained through field research with an anthropological approach. Based on the data found by the researchers, it can be concluded that the recitation of Tafsi<r Al-Sa'di< was held at the Mustaqbil Mosque, Bhinteng Hamlet, Prenduan Village, Pragaan District, Sumenep Regency, East Java, getting a positive response from the congregation. The participants liked this recitation because the way of delivering K.H'Aini felt quite clear and easy to understand. This recitation has a positive impact as felt by the recitation of the jama'ah namely, increasing knowledge, increasing faith. Also a positive impact on the mosque is the increase in the congregation of fardhu prayers. Jama'ah who take part in the Tafsi<r Al-Sa'di< recitation at the Mustaqbil Mosque, are motivated by three main things namely, motivational cognitive needs to gain understanding and knowledge, then there is a need for self-esteem namely wanting to be a role model for the family, also the need to have , to be part of a group and establish relationships with others.